Exosomes: A New Pathway for Cancer Drug Resistance - Zhong, Yunbin; Li, Haibo; Li, Peiwen; Chen, Yong; Zhang, Mengyao; Yuan, Zhendong; Zhang, Yufang; Xu, Zhijie; Luo, Geng; Fang, Yuan; Li, Xu (Frontiers in Oncology, 2021)
Exosomes are extracellular vesicles (EVs) that are secreted by multiple cell types into body fluids. The exosomes are enriched in bioactive molecules, although their exact contents depend on the parental cells. Studies show that exosomes in the tumor microenvironment affect tumor growth, metastasis and drug resistance by mediating intercellular communication and transport of specific molecules, although the exact mechanisms need to investigated further. In this review, we have summarized the current research on the relationship between tumor drug resistance and exosomes, and discussed the potential applications of exosomes as diagnostic biomarkers and therapeutic targets.